Practices of Multiple Intelligences Instruction and Teaching Performance of Public Elementary School Teachers - Lennie M. Badajos (Philippine Social Science Journal, 1970)
Research studies have explored the effects of multiple intelligences (MI) theory on the academic achievement of students. Teachers who based their instructional practices on MI theory have more authentic classrooms, and students are more genuinely engaged in class. This quantitative study determined the associations between demographic variables, the extent of multiple intelligences instructional practices, and the level of teaching performance of 178 public elementary school teachers. Using an adapted instrument, and rating form, the data were collected and were analyzed using mean, standard deviation, and Pearson r. The findings showed a significant correlation between educational attainment and years of service of teachers and eight types of multiple intelligences instructional practices.  Likewise, teaching performance was associated with variables such as age and years of service. On the other hand, mathematical and naturalistic multiple intelligences instructional practices were also related to teaching performance. Generally, results showed no correlation between multiple intelligences instructional practices and teaching performance of the teachers.